Solid-state fermentation with Rhizopus oligosporus RT-3 enhanced the nutritional properties of soybeans - Zhang, Yongzhu; Wei, Ruicheng; Azi, Fidelis; Jiao, Linshu; Wang, Heye; He, Tao; Liu, Xianjin; Wang, Ran; Lu, Baiyi (Frontiers in Nutrition, 2022)
Fermented soybean products are favorite foods worldwide because of their nutritional value and health effects. In this study, solid-state fermentation (SSF) of soybeans with Rhizopus oligosporus RT-3 was performed to investigate its nutraceutical potential. A rich enzyme system was released during SSF. Proteins were effectively transformed into small peptides and amino acids. The small peptide content increased by 13.64 times after SSF for 60 h. The antioxidant activity of soybeans was enhanced due to the release of phenolic compounds. The soluble phenolic content increased from 2.55 to 9.28 gallic acid equivalent mg/g after SSF for 60 h and exhibited high correlations with microbial enzyme activities during SSF. The potential metabolic pathways being triggered during SSF indicated that the improved nutritional composition of soybean attributed to the biochemical reactions catalyzed by microbial enzymes. These findings demonstrated that SSF could evidently improve the nutritional value and prebiotic potential of soybeans.